Posterior teeth angulation in non-extraction and extraction treatment of anterior open-bite patients - Guilherme Janson; Mayara Rizzo; Vinicius Laranjeira; Daniela Gamba Garib; Fabricio Pinelli Valarelli (SpringerOpen, 2017)
Abstract Backgound This study cephalometrically evaluated the posterior teeth angulation changes of anterior open-bite non-extraction and extraction treatment in the permanent dentition, with anterior vertical elastics. Methods The sample consisted of initial and final lateral headfilms of 60 patients divided into 2 groups: Group 1 consisted of 30 patients treated with non-extraction with an initial mean age of 15.26 years and treated with fixed appliances for a mean period of 2.46 years. Group 2 consisted of 30 patients treated with extractions, with an initial mean age of 14.03 years, and treated with fixed appliances for a mean period of 2.49 years. Within-group treatment changes were evaluated with paired t tests. Results were considered statistically significant at P < 0.05. Results The mandibular posterior teeth were significantly uprighted in both groups with both treatment protocols. Conclusions Correction of anterior open bite with either non-extraction or extractions with continuous archwires and vertical anterior elastics uprights the mandibular posterior teeth.